Problems repairing architectural monuments in Uzbekistan - Islamov Feruz Hashimovich (Genius Journals, 2022)
This article discusses the renovation of architectural buildings in Uzbekistan and its current problems
Keywords: Historical and cultural position; monumental monument; tourism